Optimal electrical load for peak power of a thermoelectric module with a solar electric application - Lesage, Frédéric J.; Pelletier, Rémi; Fournier, Luc; Sempels, Éric V. (Energy conversion and management, 2013)
•A thermoelectric module is tested under increasing electrical load resistance.•Optimal electrical load to internal load is invariant w.r.t. thermal input.•Relation describing thermopower near peak power is presented.•Load matching achieves less than maximum thermopower.•Novel solar thermoelectric conversion method is tested and reported. This paper builds upon the recent progress made in the field of thermoelectric energy conversion when using Bismuth Telluride Bi2Te3 semiconductor modules. These commercially available modules have been the subject of many recent studies in which the common goal is to better understand their thermoelectric behavior when converting a low cost heat source to electricity. The present experimental work investigates the thermopower properties of a single module relative to the electrical load resistance with the use of two experimental apparatuses. The first test stand is built with a precision control of the injection and rejection of heat to and from the module; the second test stand is a novel demonstration of the module’s application to thermoelectric solar energy conversion. The thermopower characteristics of the module are measured over a wide range of thermal input conditions. The results highlight the importance in calibrating to an optimal electrical load for peak power output. A normalized thermopower theoretical evolution curve relative to load resistance is presented. Furthermore, a method of thermoelectric recovery of solar radiation is demonstrated using laboratory controlled working conditions.